TAFSSA on-farm research trials Bangladesh: Protocol for field implementation - Cheesman, Stephanie; Islam, Saiful; Alanuzzaman Kurishi, A.S.M.; Hossain, Shakhawat; Ferdous, Zannatul; Huda, Md. Shamsul; Gathala, Mahesh Kumar; Krupnik, Timothy J. (International Maize and Wheat Improvement Center, 2022)
On-farm research trials are part of TAFSSA's Work Package 2 (WP2) activities. WP2 emphasizes farm- and landscape-level interdisciplinary research to identify strategies to increase farmers' profits and nutritional yields, conserve resources, and maintain or enhance ecological services, while also mitigating greenhouse gas (GHC) emissions from farms and agricultural landscapes. Going beyond typical agriculture-nutrition programs in South Asia, we explore field- and landscape-scale crop and animal farm diversification options supporting multiple benefits, including potential nutritional yield, across environmental and socio-economic gradients of rice-based farming systems. Rangpur and Rajshahi divisions in the north of Bangladesh have been selected as learning sites based on key information on food and nutrition security gaps, environmental stresses and climate challenges, as well as the prevalence of commodities and farming systems which offer the greatest potential to achieve TAFSSA's outcomes.